A deep ultraviolet vertical structure light emitting diode and a preparation method thereof
Patent Information
- Application Number
- CN202610924469.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-25
- Publication Date
- 2026-10-27
AI Technical Summary
[0008]本申请提供一种深紫外垂直结构发光二极管及其制备方法,旨在解决现有垂直结构发光二极管制备时采用AlN作为激光剥离时,容易发生吸收激光不完全,造成外延层损伤,AlN分解后残留的Al难以去除,致使大面积衬底难以剥离,衬底剥离后需要刻蚀到n-AlGaN层,导致AlGaN外延层的应力状态发生剧烈变化,引入较大的残余张应力,引起薄膜开裂和缺陷产生,导致现有工艺良率和器件可靠性较低的问题
[0035]本申请的有益效果包括:本申请所述深紫外垂直结构发光二极管制备时通过在衬底与AlN层之间引入剥离层(GaN),充分利用GaN禁带宽度窄、对紫外激光吸收效率高的特性,实现蓝宝石衬底的高效、低损伤剥离;同时,GaN分解生成的Ga金属熔点低(约30℃),易于去除,避免了AlN直接剥离时Al残留难以去除的问题;且有效缓解剥离后应力突变、薄膜开裂的问题。
Smart Images

Figure CN122995352A_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the field of light-emitting diode technology, specifically relating to a deep ultraviolet vertical structure light-emitting diode and its fabrication method. Background Technology
[0002] In recent years, AlGaN-based deep ultraviolet (DUV) LEDs have demonstrated application potential in fields such as sterilization, disinfection, biomedicine, and water purification due to their advantages including low power consumption, high portability, long lifespan, and wavelength tunability, becoming one of the research hotspots in the semiconductor optoelectronics field. However, compared with traditional blue LEDs, the external quantum efficiency of DUV LEDs is still relatively low, which restricts the large-scale commercialization of DUV LEDs.
[0003] Because the p-GaN contact layer at the top of the epitaxial structure of deep ultraviolet LEDs has a very strong absorption effect on ultraviolet light, photons can hardly be emitted from the top. Sapphire has good transmittance for short-wavelength ultraviolet light. Therefore, the mainstream structure of deep ultraviolet LED chips is currently the flip-chip structure. However, this structure has disadvantages such as low electro-optical conversion efficiency (generally below 10%), poor heat dissipation performance, and short lifespan.
[0004] As an alternative, the vertical structure employs a lift-off technique to remove the thermally inert sapphire substrate, allowing the p-type electrode of the device to form a direct, large-area contact with the bonded, highly thermally conductive substrate, thereby achieving efficient heat dissipation. Compared to the flip-chip structure, the vertical structure can improve the device's output power and lifespan.
[0005] Currently, laser lift-off technology has been widely used in the lift-off of sapphire substrates for blue and near-ultraviolet LEDs. This is because blue and near-ultraviolet LEDs typically use GaN as the epitaxial growth template layer, and GaN is also used as the laser lift-off layer. During laser irradiation, GaN undergoes thermal decomposition to generate nitrogen gas and metallic gallium. Since gallium has a melting point of only about 30°C, the nitrogen gas escapes, thus achieving mechanical separation between the GaN epitaxial layer and the sapphire substrate. GaN has a narrower bandgap than sapphire and AlGaN, allowing it to fully absorb laser energy, thus facilitating complete lift-off.
[0006] Deep ultraviolet (DUV) LEDs utilize high-Al content AlGaN for their n-type layer, active region, and p-type layer. Introducing a GaN layer between the high-Al content AlGaN and the sapphire substrate generates significant tensile stress on the upper film, leading to severe epitaxial layer cracking. To avoid this, high-Al content AlGaN is typically grown on an AlN template. However, AlN has a larger bandgap than AlGaN, making it prone to incomplete laser absorption when used as a laser lift-off layer, resulting in epitaxial layer damage. Furthermore, the residual Al metal after AlN decomposition has a high melting point and is difficult to remove, hindering large-area substrate lift-off. Therefore, vertical-structure DUV LEDs mostly employ AlN, high-Al content AlGaN, or an AlN / AlGaN superlattice (SL) as the lift-off layer, combined with a high-energy-density excimer laser as the light source for substrate lift-off.
[0007] Existing vertical deep ultraviolet LEDs typically employ the following process route: First, an AlN buffer layer, an n-AlGaN layer, a multiple quantum well (MQW) active layer, an electron blocking layer (EBL), a p-AlGaN layer, and a p-GaN contact layer are sequentially grown on a sapphire substrate. Then, a p-type electrode is bonded to a new thermally conductive substrate using a bonding agent. Subsequently, the sapphire substrate is removed using laser irradiation. Finally, the bottom n-AlGaN layer is etched to expose it, and an n-type electrode is directly fabricated on top of it. However, this process route requires etching down to the n-AlGaN layer after substrate removal, which completely releases the compressive stress originally constrained in the AlGaN epitaxial layer, introducing instead significant residual tensile stress. This drastic change in stress state directly affects the band structure of the active layer quantum well, leading to thin film cracking and defects, severely impacting device yield and reliability. Summary of the Invention
[0008] This application provides a deep ultraviolet vertical structure light-emitting diode and its fabrication method, aiming to solve the problems of incomplete laser absorption and epitaxial layer damage that easily occur when AlN is used as the laser lift-off material in the fabrication of existing vertical structure light-emitting diodes. After AlN decomposition, the residual Al is difficult to remove, making it difficult to lift off large-area substrates. After the substrate is lifted off, it is necessary to etch down to the n-AlGaN layer, which causes a drastic change in the stress state of the AlGaN epitaxial layer, introducing large residual tensile stress, causing thin film cracking and defects, resulting in low yield and device reliability of existing processes.
[0009] The first aspect of this application provides a deep ultraviolet vertical structure light-emitting diode, including an electrode, a passivation layer, an AlN layer, an n-AlGaN layer, a multi-quantum-well active layer, an electron blocking layer, a p-AlGaN layer, and a bonding substrate; The electrodes include an n-type first electrode, an n-type second electrode, a p-type first electrode, a p-type second electrode, and a p-type third electrode; the passivation layer includes a first passivation layer, a second passivation layer, and a third passivation layer; The p-AlGaN layer, electron blocking layer, multi-quantum well active layer, n-AlGaN layer and AlN layer are sequentially overlapped; The p-AlGaN layer has a first groove and a second groove. The first groove penetrates the p-AlGaN layer, the electron blocking layer, the multi-quantum well active layer, and part of the n-AlGaN layer. The second groove penetrates the p-AlGaN layer, the electron blocking layer, the multi-quantum well active layer, the n-AlGaN layer, and the AlN layer. The first passivation layer covers the surface of the p-AlGaN layer, the sidewalls of the first groove and the sidewalls of the second groove; a third groove is provided on the first passivation layer, the third groove penetrates the first passivation layer to expose the p-AlGaN layer, and the third groove is located between the first groove and the second groove; The first groove is filled with an n-type first electrode, which is in ohmic contact with the n-AlGaN layer; the second groove is filled with a p-type second electrode, and the third groove is filled with a p-type first electrode, which is in ohmic contact with the p-AlGaN layer; the p-type second electrode extends to the surface of the first passivation layer and is electrically connected to the p-type first electrode. The second passivation layer covers the first passivation layer, the p-type first electrode, and the p-type second electrode; The n-type second electrode covers the second passivation layer and the n-type first electrode, and the n-type second electrode is connected to the n-type first electrode; the bonding substrate and the n-type second electrode are fixedly connected. The third passivation layer covers the surface of the AlN layer, and the p-type third electrode covers the third passivation layer and is connected to the p-type second electrode.
[0010] According to some embodiments of the deep ultraviolet vertical structure light-emitting diode described in this application, the electrode includes one or more of gold, platinum, nickel, titanium, aluminum, chromium, palladium, silver, indium, copper and tin.
[0011] According to some embodiments of the deep ultraviolet vertical structure light-emitting diode described in this application, the passivation layer includes a single-layer or multi-layer composite layer composed of one or more of SiO2, Si3N4, ZrO2, and Al2O3.
[0012] According to some embodiments of the deep ultraviolet vertical structure light-emitting diode described in this application, the bonding substrate layer includes a silicon substrate, a copper substrate, a ceramic substrate, or a metal composite substrate.
[0013] According to some embodiments of the deep ultraviolet vertical structure light-emitting diode described in this application, the thickness of the AlN layer is 50nm-4000nm.
[0014] According to some embodiments of the deep ultraviolet vertical structure light-emitting diode described in this application, the thickness of the n-AlGaN layer is 1-3 μm.
[0015] According to some embodiments of the deep ultraviolet vertical structure light-emitting diode described in this application, the thickness of the multi-quantum well active layer is 30-100 nm.
[0016] According to some embodiments of the deep ultraviolet vertical structure light-emitting diode described in this application, the thickness of the electron blocking layer is 20-50 nm.
[0017] According to some embodiments of the deep ultraviolet vertical structure light-emitting diode described in this application, the thickness of the p-AlGaN layer is 100-200 nm.
[0018] According to some embodiments of the deep ultraviolet vertical structure light-emitting diode described in this application, the thickness of the first passivation layer is 100-300 nm.
[0019] According to some embodiments of the deep ultraviolet vertical structure light-emitting diode described in this application, the thickness of the second passivation layer is 200-500 nm.
[0020] According to some embodiments of the deep ultraviolet vertical structure light-emitting diode described in this application, the thickness of the third passivation layer is 500-1000 nm.
[0021] According to some embodiments of the deep ultraviolet vertical structure light-emitting diode described in this application, the thickness of the n-type first electrode is 30-120 nm.
[0022] According to some embodiments of the deep ultraviolet vertical structure light-emitting diode described in this application, the thickness of the n-type second electrode is 2μm-4μm.
[0023] According to some embodiments of the deep ultraviolet vertical structure light-emitting diode described in this application, the thickness of the p-type first electrode is 50-200 nm.
[0024] According to some embodiments of the deep ultraviolet vertical structure light-emitting diode described in this application, the thickness of the p-type second electrode is 600-1500 nm.
[0025] According to some embodiments of the deep ultraviolet vertical structure light-emitting diode described in this application, the thickness of the p-type third electrode is 1μm-2μm.
[0026] A second aspect of this application provides a method for fabricating the deep ultraviolet vertical structure light-emitting diode described in the first aspect of this application, comprising the following steps: (1) Epitaxial growth of a release layer, an AlN layer, an n-AlGaN layer, a multi-quantum-well active layer, an electron blocking layer and a p-AlGaN layer is performed sequentially on the substrate; (2) A first groove and a second groove are etched on the p-AlGaN layer, such that the first groove penetrates the p-AlGaN layer, the electron blocking layer, the multi-quantum well active layer and part of the n-AlGaN layer; the second groove penetrates the p-AlGaN layer, the electron blocking layer, the multi-quantum well active layer, the n-AlGaN layer and the AlN layer, exposing the release layer; (3) A first passivation layer is deposited on the surface of the p-AlGaN layer, the first groove and the second groove, and the first passivation layer is etched to expose the bottom n-AlGaN layer of the first groove and the bottom stripping layer of the second groove, and the first passivation layer is etched to expose the p-AlGaN layer to form a third groove, the third groove being located between the first groove and the second groove. (4) An n-type first electrode is prepared in the first groove, so that the n-type first electrode fills the first groove and extends out the first passivation layer, and the n-type first electrode and the n-AlGaN layer are in ohmic contact. After preparation, a first annealing treatment is performed. Then, a p-type first electrode is prepared in the third groove, so that the p-type first electrode fills the third groove and extends out the first passivation layer, and the p-type first electrode and the p-AlGaN layer are in ohmic contact. After preparation, a second annealing treatment is performed. Then, a p-type second electrode is prepared in the second groove, so that the p-type second electrode fills the second groove and extends out the first passivation layer and is electrically connected to the p-type first electrode. (5) A second passivation layer is deposited on the surface of the n-shaped first electrode, the p-shaped first electrode, the p-shaped second electrode and the first passivation layer, the second passivation layer is etched to expose the n-shaped first electrode, an n-shaped second electrode is prepared on the n-shaped first electrode, and the n-shaped second electrode is extended to cover the second passivation layer. (6) A metal layer is deposited on the surface of the bonding substrate, and the n-type second electrode and the bonding substrate are bonded by metal bonding process; (7) The substrate side is irradiated with a laser to thermally decompose the release layer and peel off the substrate layer, exposing the bare surface of the AlN layer and the p-type second electrode; a third passivation layer is deposited on the surface of the AlN layer and the bare p-type second electrode, the third passivation layer is etched to expose the p-type second electrode, and then a p-type third electrode is prepared on the bare p-type second electrode, and the p-type third electrode is extended to cover the third passivation layer.
[0027] According to some embodiments of the preparation method described in this application, in step (4), the temperature of the first annealing is 850-900℃ and the time is 30-60s.
[0028] According to some embodiments of the preparation method described in this application, the second annealing temperature is 500-550°C and the time is 30-60 seconds.
[0029] According to some embodiments of the preparation method described in this application, in step (6), the metal layer includes one or more of Ti layer, Au layer and In layer.
[0030] According to some embodiments of the preparation method described in this application, the bonding temperature is 250-350℃, the bonding pressure is 1MPa-5MPa, and the bonding time is 10-30min.
[0031] According to some embodiments of the preparation method described in this application, the substrate includes a sapphire substrate.
[0032] According to some embodiments of the preparation method described in this application, the stripping layer includes a GaN stripping layer.
[0033] According to some embodiments of the preparation method described in this application, the thickness of the release layer is 25-90 nm.
[0034] According to some embodiments of the preparation method described in this application, in step (7), the wavelength of the laser is 193nm-355nm and the energy density is 200mJ / cm². 2 -1000 mJ / cm 2 Preferably, the laser is a KrF laser with a wavelength of 248 nm.
[0035] The beneficial effects of this application include: when fabricating the deep ultraviolet vertical structure light-emitting diode described in this application, a release layer (GaN) is introduced between the substrate and the AlN layer, which fully utilizes the characteristics of GaN's narrow bandgap and high absorption efficiency for ultraviolet lasers to achieve efficient and low-damage release of the sapphire substrate; at the same time, the Ga metal generated by GaN decomposition has a low melting point (about 30°C) and is easy to remove, avoiding the problem of difficult removal of Al residue when AlN is directly released; and effectively alleviating the problems of stress change and film cracking after release. Attached Figure Description
[0036] Figure 1 This is a schematic diagram of the epitaxial layer grown on a sapphire substrate during the fabrication of the deep ultraviolet vertical structure light-emitting diode described in Embodiment 1 of this application; Figure 2 This is a schematic diagram of the structure after etching to form the first and second grooves during the fabrication of the deep ultraviolet vertical structure light-emitting diode described in Embodiment 1 of this application; Figure 3 This is a schematic diagram of the structure of the deep ultraviolet vertical structure light-emitting diode after the first passivation layer is formed during the fabrication of the diode described in Embodiment 1 of this application; Figure 4 This is a schematic diagram of the structure after the third groove is formed during the fabrication of the deep ultraviolet vertical structure light-emitting diode described in Embodiment 1 of this application; Figure 5 This is a schematic diagram of the structure of the deep ultraviolet vertical structure light-emitting diode after forming an n-type first electrode, a p-type first electrode, and a p-type second electrode during the fabrication of the deep ultraviolet vertical structure light-emitting diode described in Embodiment 1 of this application. Figure 6 This is a schematic diagram of the structure of the deep ultraviolet vertical structure light-emitting diode after the second passivation layer is formed during the fabrication of the diode described in Embodiment 1 of this application; Figure 7 This is a schematic diagram of the structure of the deep ultraviolet vertical structure light-emitting diode after etching and exposing the n-type first electrode during fabrication as described in Embodiment 1 of this application; Figure 8 This is a schematic diagram of the structure after forming the n-type second electrode during the fabrication of the deep ultraviolet vertical structure light-emitting diode described in Embodiment 1 of this application; Figure 9 This is a schematic diagram of the bonding structure between the n-type second electrode and the bonding substrate during the fabrication of the deep ultraviolet vertical structure light-emitting diode described in Embodiment 1 of this application; Figure 10 This is a schematic diagram of the structure of the sapphire substrate after laser lift-off during the fabrication of the deep ultraviolet vertical structure light-emitting diode as described in Embodiment 1 of this application; Figure 11 This is a schematic diagram of the structure after the third passivation layer is formed during the fabrication of the deep ultraviolet vertical structure light-emitting diode as described in Embodiment 1 of this application; Figure 12 This is a schematic diagram of the deep ultraviolet vertical structure light-emitting diode after etching to expose the p-type second electrode during fabrication as described in Embodiment 1 of this application; Figure 13 This is a schematic diagram of the deep ultraviolet vertical structure light-emitting diode described in Embodiment 1 of this application.
[0037] In the figure: 1. Substrate; 2. Release layer; 3. AlN layer; 4. n-AlGaN layer; 5. Multiple quantum well active layer; 6. Electron blocking layer; 7. p-AlGaN layer; 8. First groove; 9. Second groove; 10. First passivation layer; 11. Third groove; 12. n-type first electrode; 13. p-type first electrode; 14. p-type second electrode; 15. Second passivation layer; 16. n-type second electrode; 17. Bonding substrate; 18. Third passivation layer; 19. p-type third electrode. Detailed Implementation
[0038] The embodiments of the present invention are described in detail below. These embodiments are exemplary and intended to explain the present invention, and should not be construed as limiting the present invention.
[0039] In this invention, the terms "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., refer to a specific feature, structure, material, or characteristic described in connection with that embodiment or example, which is included in at least one embodiment or example of the invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples. Moreover, without contradiction, those skilled in the art can combine and integrate the different embodiments or examples described in this specification, as well as the features of different embodiments or examples.
[0040] This application provides a deep ultraviolet vertical structure light-emitting diode, including an electrode, a passivation layer, an AlN layer, an n-AlGaN layer, a multi-quantum-well active layer, an electron blocking layer, a p-AlGaN layer, and a bonding substrate; The electrodes include an n-type first electrode, an n-type second electrode, a p-type first electrode, a p-type second electrode, and a p-type third electrode; the passivation layer includes a first passivation layer, a second passivation layer, and a third passivation layer; The p-AlGaN layer, electron blocking layer, multi-quantum well active layer, n-AlGaN layer and AlN layer are sequentially overlapped; The p-AlGaN layer has a first groove and a second groove. The first groove penetrates the p-AlGaN layer, the electron blocking layer, the multi-quantum well active layer, and part of the n-AlGaN layer. The second groove penetrates the p-AlGaN layer, the electron blocking layer, the multi-quantum well active layer, the n-AlGaN layer, and the AlN layer. The first passivation layer covers the surface of the p-AlGaN layer, the sidewalls of the first groove and the sidewalls of the second groove; a third groove is provided on the first passivation layer, the third groove penetrates the first passivation layer to expose the p-AlGaN layer, and the third groove is located between the first groove and the second groove; The first groove is filled with an n-type first electrode, which is in ohmic contact with the n-AlGaN layer; the second groove is filled with a p-type second electrode, and the third groove is filled with a p-type first electrode, which is in ohmic contact with the p-AlGaN layer; the p-type second electrode extends to the surface of the first passivation layer and is electrically connected to the p-type first electrode. The second passivation layer covers the first passivation layer, the p-type first electrode, and the p-type second electrode; The n-type second electrode covers the second passivation layer and the n-type first electrode, and the n-type second electrode is electrically connected to the n-type first electrode; the bonding substrate and the n-type second electrode are fixedly connected. The third passivation layer covers the surface of the AlN layer, and the p-type third electrode covers the third passivation layer and is electrically connected to the p-type second electrode.
[0041] The deep ultraviolet vertical structure light-emitting diode introduces a release layer (GaN) between the substrate and the AlN layer, making full use of GaN's narrow bandgap and high ultraviolet laser absorption efficiency to achieve efficient and low-damage release of the sapphire substrate. At the same time, the Ga metal generated by GaN decomposition has a low melting point (about 30°C) and is easy to remove, avoiding the problem of difficult removal of Al residue when AlN is directly released; and effectively alleviates the problems of stress change and film cracking after release.
[0042] In some embodiments of this application, the electrode includes one or more of gold, platinum, nickel, titanium, aluminum, chromium, palladium, silver, indium, copper, and tin.
[0043] In some embodiments of this application, the passivation layer comprises a single-layer or multi-layer composite layer composed of one or more of SiO2, Si3N4, ZrO2, and Al2O3.
[0044] In some embodiments of this application, the bonding substrate layer includes a silicon substrate, a copper substrate, a ceramic substrate, or a metal composite substrate. The bonding substrate is a material with good thermal conductivity.
[0045] In some embodiments of this application, the thickness of the AlN layer is 50nm-4000nm; for example, 50nm, 100nm, 500nm, 800nm, 1000nm, 1600nm, 2000nm, 2800nm, 3200nm, 3800nm, 4000nm, etc. The AlN layer needs to have sufficient thickness to provide effective stress buffering after substrate peeling, while ensuring the crystal quality of epitaxial growth. On the one hand, the AlN layer serves as a template layer for the growth of n-AlGaN layers, providing a high-quality crystal foundation; on the other hand, it acts as a stress buffer layer after substrate peeling, buffering sudden stress changes.
[0046] In some embodiments of this application, the thickness of the n-AlGaN layer is 1-3 μm; the Al composition percentage in the n-AlGaN layer is 50%-70%, and the Si doping concentration is 1×10⁻⁶. 18 cm -3 -1×10 20 cm -3 .
[0047] In some embodiments of this application, the thickness of the multi-quantum well active layer is 30-100 nm; the percentage of Al component in the multi-quantum well active layer is 20%-70%, and the percentage of Al component in the quantum barrier is 50%-90%, thereby achieving luminescence in the deep ultraviolet band (wavelength 220 nm-280 nm).
[0048] In some embodiments of this application, the thickness of the electron blocking layer is 20-50 nm; the percentage of Al composition in the electron blocking layer is 50%-90%, and the Mg doping concentration is 1×10⁻⁶. 17 cm -3 -1×10 21 cm -3 It is used to block the leakage of electrons from the active region to the p-type layer, thereby improving the carrier injection efficiency.
[0049] In some embodiments of this application, the thickness of the p-AlGaN layer is 100-200 nm; the Al composition in the p-AlGaN layer is 0-60%, and the Mg doping concentration is 1×10⁻⁶. 17 cm -3 -1×10 21 cm -3 .
[0050] In some embodiments of this application, the thickness of the first passivation layer is 100-300 nm; for example, 100 nm, 120 nm, 150 nm, 180 nm, 230 nm, 260 nm, 300 nm, etc. The first passivation layer protects the surface of the epitaxial layer and provides insulation between the electrodes to prevent leakage.
[0051] In some embodiments of this application, the thickness of the second passivation layer is 200-500 nm; for example, 200 nm, 250 nm, 300 nm, 380 nm, 410 nm, 460 nm, 500 nm, etc. The second passivation layer also has the effect of protecting the electrode and the epitaxial layer, preventing short circuits and leakage.
[0052] In some embodiments of this application, the thickness of the third passivation layer is 500-1000nm; for example, 500nm, 650nm, 730nm, 820nm, 900nm, 960nm, 1000nm, etc.
[0053] In some embodiments of this application, the thickness of the n-type first electrode is 30-120 nm; for example, 30 nm, 50 nm, 67 nm, 85 nm, 100 nm, 105 nm, 112 nm, 120 nm, etc.
[0054] In some embodiments of this application, the thickness of the n-type second electrode is 2μm-4μm; for example, 2μm, 2.5μm, 3μm, 3.8μm, 4μm, etc.
[0055] In some embodiments of this application, the thickness of the p-type first electrode is 50-200 nm; for example, 50 nm, 80 nm, 100 nm, 120 nm, 150 nm, 200 nm, etc.
[0056] In some embodiments of this application, the thickness of the p-type second electrode is 600-1500 nm; for example, 600 nm, 800 nm, 1000 nm, 1200 nm, 1500 nm, etc.
[0057] In some embodiments of this application, the thickness of the p-type third electrode is 1μm-2μm; for example, 1μm, 1.2μm, 1.5μm, 1.8μm, 2μm, etc.
[0058] This application also provides a method for fabricating the deep ultraviolet vertical structure light-emitting diode described in the first aspect of this application, comprising the following steps: (1) Epitaxial growth of a release layer, an AlN layer, an n-AlGaN layer, a multi-quantum-well active layer, an electron blocking layer and a p-AlGaN layer is performed sequentially on the substrate; (2) A first groove and a second groove are etched on the p-AlGaN layer, such that the first groove penetrates the p-AlGaN layer, the electron blocking layer, the multi-quantum well active layer and part of the n-AlGaN layer; the second groove penetrates the p-AlGaN layer, the electron blocking layer, the multi-quantum well active layer, the n-AlGaN layer and the AlN layer, exposing the release layer; (3) A first passivation layer is deposited on the surface of the p-AlGaN layer, the first groove and the second groove, and the first passivation layer is etched to expose the bottom n-AlGaN layer of the first groove and the bottom stripping layer of the second groove, and the first passivation layer is etched to expose the p-AlGaN layer to form a third groove, the third groove being located between the first groove and the second groove. (4) An n-type first electrode is prepared in the first groove, so that the n-type first electrode fills the first groove and extends out the first passivation layer, and the n-type first electrode and the n-AlGaN layer are in ohmic contact. After preparation, a first annealing treatment is performed. Then, a p-type first electrode is prepared in the third groove, so that the p-type first electrode fills the third groove and extends out the first passivation layer, and the p-type first electrode and the p-AlGaN layer are in ohmic contact. After preparation, a second annealing treatment is performed. Then, a p-type second electrode is prepared in the second groove, so that the p-type second electrode fills the second groove and extends out the first passivation layer and is electrically connected to the p-type first electrode. (5) A second passivation layer is deposited on the surface of the n-shaped first electrode, the p-shaped first electrode, the p-shaped second electrode and the first passivation layer, the second passivation layer is etched to expose the n-shaped first electrode, an n-shaped second electrode is prepared on the n-shaped first electrode, and the n-shaped second electrode is extended to cover the second passivation layer. (6) A metal layer is deposited on the surface of the bonding substrate, and the n-type second electrode and the bonding substrate are bonded by metal bonding process; (7) The substrate side is irradiated with a laser to thermally decompose the release layer and peel off the substrate layer, exposing the bare surface of the AlN layer and the p-type second electrode; a third passivation layer is deposited on the surface of the AlN layer and the bare p-type second electrode, the third passivation layer is etched to expose the p-type second electrode, and then a p-type third electrode is prepared on the bare p-type second electrode, and the p-type third electrode is extended to cover the third passivation layer.
[0059] The deep ultraviolet vertical structure light-emitting diode described in this application introduces a release layer (GaN layer) between the substrate and the AlN buffer layer during fabrication. Utilizing the characteristics of GaN—narrow bandgap, easy laser absorption, and low melting point of its decomposition products (Ga)—GaN replaces the traditional high-Al content AlN release layer, solving the technical problems of difficult substrate stripping, significant damage, and difficulty in removing residual metals in deep ultraviolet LEDs.
[0060] In the fabrication of the deep ultraviolet vertical structure light-emitting diode described in this application, after laser lift-off of the substrate, the complete AlN layer is retained (without etching removal), and the passivation layer and electrodes are directly fabricated on the AlN layer. Compared with the traditional process that requires etching AlN to expose n-AlGaN after lift-off, the fabrication method described in this application uses the retained AlN layer as a stress buffer medium to suppress the tensile stress abrupt change caused by the release of substrate constraints, and prevent quantum well band distortion and epitaxial layer cracking.
[0061] In some embodiments of this application, the epitaxial growth of a release layer, an AlN layer, an n-AlGaN layer, a multi-quantum-well active layer, an electron blocking layer, and a p-AlGaN layer on a substrate can be performed using an MOCVD system, with trimethylgallium (TMGa), trimethylaluminum (TMAl), ammonia (NH3), etc., as reaction sources, and silane (SiH4) and magnesium pyrocene (Cp2Mg) as n-type and p-type doping sources, respectively.
[0062] In some embodiments of this application, the etching process for forming the grooves may be photolithography and / or dry etching (inductively coupled plasma (ICP) etching).
[0063] In some embodiments of this application, the process for depositing the passivation layer may be plasma-enhanced chemical vapor deposition (PECVD) or atomic layer deposition (ALD).
[0064] In some embodiments of this application, the process for preparing the electrode includes electron beam evaporation or electroplating.
[0065] In some embodiments of this application, in step (4), the temperature of the first annealing is 850-900℃, such as 850℃, 880℃, 900℃, etc., and the time is 30-60s; such as 30s, 35s, 40s, 43s, 48s, 50s, 60s, etc.
[0066] In some embodiments of this application, the temperature of the second annealing is 500-550°C, such as 500°C, 520°C, 550°C, etc., and the time is 30-60 seconds.
[0067] In some embodiments of this application, in step (6), the metal layer includes one or more of Ti, Au and In layers.
[0068] In some embodiments of this application, the bonding temperature is 250-350℃, such as 250℃, 280℃, 300℃, 320℃, 350℃, etc., the bonding pressure is 1MPa-5MPa, such as 1MPa, 2MPa, 3MPa, 5MPa, etc., and the bonding time is 10-30min, such as 10min, 15min, 20min, 25min, 28min, 30min, etc.
[0069] In some embodiments of this application, the substrate includes a sapphire substrate.
[0070] In some embodiments of this application, the release layer includes a GaN release layer. GaN has a narrow bandgap, readily absorbs laser light, and its decomposition products (Ga) have low melting points. It can replace traditional high-Al content AlN release layers, solving the technical problems of difficult release, significant damage, and difficulty in removing residual metals from deep ultraviolet LED substrates.
[0071] In some embodiments of this application, the thickness of the release layer is 25-90 nm. This thickness range is based on the following considerations: ① A thickness ≥ 25 nm ensures that the GaN layer forms a continuous and flat two-dimensional film on the sapphire substrate, guaranteeing the continuous and complete decomposition of the release layer during laser lift-off; ② A thickness ≤ 90 nm ensures that the additional tensile stress introduced by GaN is low, without affecting the original stress buffering function of the AlN template layer; ③ The amount of metallic Ga generated after laser lift-off is small and easy to remove.
[0072] In some embodiments of this application, in step (7), the wavelength of the laser is 193nm-355nm and the energy density is 200mJ / cm². 2 -1000 mJ / cm 2 For example, 200mJ / cm 2 250mJ / cm 2 320mJ / cm 2 380mJ / cm 2 430mJ / cm 2 500mJ / cm 2 560mJ / cm 2 670mJ / cm 2 820mJ / cm 2 1000mJ / cm2 In a preferred embodiment, the laser is a KrF laser with a wavelength of 248 nm. The laser penetrates the substrate and is absorbed by the release layer, causing thermal decomposition of the release layer and thus peeling off the substrate. The selection of laser parameters should ensure that the release layer can fully absorb the laser energy and completely decompose, while avoiding thermal damage to the AlN and AlGaN layers.
[0073] The deep ultraviolet vertical structure light-emitting diode described in this application employs an inverted vertical structure process path, omitting the step of etching to remove the AlN layer after lift-off, thus retaining the complete AlN layer as a stress buffer layer. This avoids the problem of incomplete laser absorption and epitaxial layer damage that easily occurs when using AlN as a laser lift-off layer.
[0074] The current conduction path of the deep ultraviolet vertical structure light-emitting diode described in this application is as follows: current is injected from the p-type third electrode and enters the p-type second electrode; the p-type second electrode extends laterally and is electrically connected to the p-type first electrode; the current is injected into the p-AlGaN layer through the p-type first electrode, and flows sequentially through the EBL layer and the MQW layer, where electrons and holes recombine and emit light in the MQW layer; the current continues downward into the n-AlGaN layer and is laterally collected by the n-type first electrode; the current is then led out to the bonding substrate through the n-type second electrode (metal bonding layer), completing the entire vertical conduction circuit.
[0075] The deep ultraviolet vertical structure light-emitting diode described in this application forms a unique current path structure of "bonding substrate-n electrode-epitaxy layer-AlN layer-p electrode". Since the n-type electrode is led out through the bonding substrate and the p-type electrode is led out from the AlN side, vertical current injection is achieved, while completely eliminating the need for etching the AlN layer after stripping. This not only simplifies the process but also allows the AlN layer to be retained to buffer stress abrupt changes, fundamentally solving the problems of thin film cracking and device reliability caused by drastic stress changes in traditional processes.
[0076] The technical solution of this application will be further described below with reference to specific embodiments.
[0077] Example 1 A method for fabricating a deep ultraviolet vertical structure light-emitting diode includes the following steps: (1) such as Figure 1 As shown, a 50nm GaN lift-off layer, a 2000nm AlN layer, a 1500nm n-AlGaN layer, a 65nm multiple quantum well (MQW) active layer, a 30nm electron blocking layer (EBL) layer, and a 150nm p-AlGaN layer were sequentially epitaxially grown on a 480μm sapphire substrate using MOCVD technology. The growth temperature of the GaN lift-off layer was 550℃, and the growth temperature of the AlN layer was 1200℃. (2) such as Figure 2 As shown, a first groove and a second groove are formed on the p-AlGaN layer by photolithography and dry etching processes. The first groove penetrates the p-AlGaN layer, the electron blocking layer, the multi-quantum well active layer, and part of the n-AlGaN layer. The second groove penetrates the p-AlGaN layer, the electron blocking layer, the multi-quantum well active layer, the n-AlGaN layer, and the AlN layer, exposing the lift-off layer. (3) such as Figure 3 As shown, a 200 nm thick SiO2 first passivation layer is deposited on the surface of the p-AlGaN layer, the first groove, and the second groove using plasma-enhanced chemical vapor deposition (PECVD). Then, photolithography and dry etching processes are used to etch and expose the bottom n-AlGaN layer of the first groove and the bottom lift-off layer of the second groove on the first passivation layer. Etching the first passivation layer to expose the p-AlGaN layer forms a third groove, which is located between the first and second grooves (e.g., ...). Figure 4 (as shown) (4) such as Figure 5 As shown, an n-type first electrode with a Ti / Al / Ti / Au multilayer structure was fabricated in the first groove using electron beam evaporation (where the thicknesses of the Ti / Al / Ti / Au multilayer electrode layers were 30 nm, 120 nm, 30 nm, and 100 nm, respectively). The n-type first electrode filled the first groove and extended a first passivation layer, ensuring ohmic contact between the n-type first electrode and the n-AlGaN layer. After fabrication, the electrode was thermally annealed at 900°C for 50 seconds to form a good ohmic contact. Then, a Ni / Au multilayer electrode was fabricated in the third groove using electron beam evaporation. A p-type first electrode with a multilayer structure (where the thickness of the Ni / Au multilayer electrode layer is 160 nm) is prepared by filling a third groove and extending a first passivation layer, and by making the p-type first electrode and the p-AlGaN layer ohmic contact. After preparation, it is thermally annealed at 500 °C for 50 s. Then, a p-type second electrode with a multilayer structure of Ni / Au (where the total thickness of the Ni / Au multilayer electrode layer is 1.2 μm) is prepared in a second groove by electron beam evaporation, and the p-type second electrode fills the second groove and extends a first passivation layer, and is electrically connected to the p-type first electrode. (5) such as Figure 6 As shown, a 300 nm thick SiO2 second passivation layer is deposited on the surfaces of the n-shaped first electrode, p-type first electrode, p-type second electrode, and first passivation layer using plasma-enhanced chemical vapor deposition (PECVD) to further protect the electrodes and epitaxial layer and prevent short circuits and leakage. Photolithography and dry etching processes are then used to etch and expose the n-shaped first electrode (e.g., ...) on the second passivation layer. Figure 7As shown); using electron beam evaporation, an n-type second electrode with an Al / Ti / Au multilayer structure (where the total thickness of the Al / Ti / Au multilayer electrode layer is 2.1 μm) is fabricated on an n-type first electrode, and the n-type second electrode is extended to cover a second passivation layer (as shown). Figure 8 As shown in the figure, the n-type second electrode serves as a metal bonding layer for subsequent bonding with the bonding substrate; (6) A Ti / Au / In metal layer (with a total thickness of 200 nm) is deposited on the surface of the silicon bonding substrate, and the n-type second electrode is bonded to the bonding substrate at a temperature of 300 °C and a pressure of 3 MPa for 20 min using a metal bonding process, so that the chip structure is firmly fixed to the silicon bonding substrate (e.g., Figure 9 (as shown) (7) An excimer laser (wavelength 248nm, energy density 250mJ / cm²) was used. 2 A KrF laser is used to irradiate the sapphire substrate. The laser light penetrates the sapphire substrate and is absorbed by the GaN lift-off layer. Upon absorbing the laser energy, the GaN lift-off layer undergoes thermal decomposition, generating nitrogen (N2) and metallic gallium (Ga). Since gallium has a melting point of only about 30°C, it exists in a liquid state under laser heating. The combined effect of the gas pressure and thermal stress generated by the escape of nitrogen gas causes the sapphire substrate to separate from the AlN layer, thus successfully lifting the sapphire substrate and exposing the surface of the AlN layer and the exposed surface of the p-type second electrode (e.g., ...). Figure 10 (as shown) (8) Clean the exposed AlN layer surface after stripping to remove any possible Ga residue. Then, use plasma-enhanced chemical vapor deposition (PECVD) to deposit a 600 nm thick SiO2 third passivation layer (e.g., ...) on the AlN layer surface and the exposed p-type second electrode surface. Figure 11 (As shown); then, photolithography and dry etching processes are used to etch and expose the p-type second electrode on the third passivation layer (as shown). Figure 12 As shown), an electron beam evaporation process is then used to fabricate a Ni / Au / Sn multilayer p-type third electrode (where the total thickness of the Ni / Au / Sn multilayer electrode layer is 1.2 μm) on the exposed p-type second electrode. The p-type third electrode is then extended to cover a third passivation layer, resulting in a deep ultraviolet vertical structure light-emitting diode (such as...). Figure 13 (As shown).
[0078] Example 2 The only difference between the deep ultraviolet vertical structure light-emitting diode fabrication method described in Example 2 and Example 1 is that the thickness of the GaN stripping layer is 25 nm during the fabrication of the deep ultraviolet vertical structure light-emitting diode in Example 2. The rest is the same as in Example 1.
[0079] Example 3 The only difference between the fabrication method of the deep ultraviolet vertical structure light-emitting diode in Example 3 and that in Example 1 is that the excimer laser energy density is 500 mJ / cm² during the fabrication of the deep ultraviolet vertical structure light-emitting diode in Example 3. 2 The rest is the same as in Example 1.
[0080] Performance Study of the Deep Ultraviolet Vertical Structure Light Emitting Diodes Described in Examples 1-3 of this Application Research Methods: Three batches of deep ultraviolet vertical structure light-emitting diodes (500 chips per batch, with a peak emission wavelength of approximately 265 nm) were fabricated using the deep ultraviolet vertical structure light-emitting diodes described in Examples 1-3 of this application, and the system performance was tested. The test results are shown in Table 1.
[0081] Table 1
[0082] As shown in Table 1, the 50 nm thickness of the release layer in Example 1 of this application matches well with the energy density of the excimer laser. The laser energy is fully absorbed, and the heat-affected zone is basically confined within the release layer, resulting in no thermal damage to the AlN layer and the epitaxial layer. After release, the surface of the AlN layer is smooth and free of residual Ga metal, facilitating subsequent passivation and electrode processing. Due to the integrity of the stress buffer layer, the absence of cracks in the epitaxial layer, and the stability of the quantum well band structure, the device exhibits the highest optical output power and the best long-term reliability.
[0083] The release layer of the deep ultraviolet vertical structure light-emitting diode described in Example 2 is too thin. The 25nm GaN layer thickness is an average value, and there may be areas where the GaN thickness is too thin, making it impossible to release in some areas. Simultaneously, the thin GaN layer allows some laser energy to easily penetrate the release layer and enter the AlN layer. AlN does not completely absorb the 248nm laser, causing photothermal energy to accumulate within the AlN layer, forming microcracks. This results in increased leakage current in some chips after subsequent passivation.
[0084] The laser energy density of the deep ultraviolet vertical structure light-emitting diode described in Example 3 is too high. Although the release layer thickness of 50 nm is suitable, it is still 500 mJ / cm. 2 The energy density far exceeds the threshold required for complete decomposition of GaN of this thickness (approximately 200-300 mJ / cm). 2 Excess energy is converted into thermal shock, causing the GaN decomposition region to experience instantaneous excessively high temperatures. The high temperature subjects the AlN layer to thermal stress, resulting in microcracks, and makes complete Ga removal difficult. Although the stripping success rate is acceptable, microscopic damage already exists inside the chip, leading to reduced luminous efficiency, significant aging degradation, and poor reliability.
[0085] Therefore, the yield, luminous efficacy, and lifetime of Examples 2 and 3 are significantly lower than those of Example 1. Example 1 used a GaN lifter layer thickness of 50 nm and a laser energy density of 250 mJ / cm². 2 This represents a superior process window, enabling high yield, high optical output power, and long lifespan simultaneously. In contrast, excessively thin release layers (25 nm) or excessively high laser energy (500 mJ / cm²) result in unfavorable conditions. 2 Both of these factors significantly degrade device performance. This verifies that the present invention addresses the limitations of the release layer thickness (25-90 nm) and laser energy density (200-500 mJ / cm²). 2 The limitation of ) is of substantial significance, and 50 nm corresponds to 250 mJ / cm 2 The preferred value is the center.
[0086] Although the above embodiments have been shown and described, it is understood that the above embodiments are exemplary and should not be construed as limiting the present invention. Any changes, modifications, substitutions and variations made to the above embodiments by those skilled in the art are within the protection scope of the present invention.
Claims
1. A deep ultraviolet vertical structure light-emitting diode, characterized in that, It includes electrodes, passivation layer, AlN layer, n-AlGaN layer, multi-quantum-well active layer, electron blocking layer, p-AlGaN layer and bonding substrate; The electrodes include an n-type first electrode, an n-type second electrode, a p-type first electrode, a p-type second electrode, and a p-type third electrode; the passivation layer includes a first passivation layer, a second passivation layer, and a third passivation layer; The p-AlGaN layer, electron blocking layer, multi-quantum well active layer, n-AlGaN layer and AlN layer are sequentially overlapped; The p-AlGaN layer has a first groove and a second groove. The first groove penetrates the p-AlGaN layer, the electron blocking layer, the multi-quantum well active layer, and part of the n-AlGaN layer. The second groove penetrates the p-AlGaN layer, the electron blocking layer, the multi-quantum well active layer, the n-AlGaN layer, and the AlN layer. The first passivation layer covers the surface of the p-AlGaN layer, the sidewalls of the first groove and the sidewalls of the second groove; a third groove is provided on the first passivation layer, the third groove penetrates the first passivation layer to expose the p-AlGaN layer, and the third groove is located between the first groove and the second groove; The first groove is filled with an n-type first electrode, which is in ohmic contact with the n-AlGaN layer; the second groove is filled with a p-type second electrode, and the third groove is filled with a p-type first electrode, which is in ohmic contact with the p-AlGaN layer. The p-type second electrode extends to the surface of the first passivation layer and is electrically connected to the p-type first electrode; The second passivation layer covers the first passivation layer, the p-type first electrode, and the p-type second electrode; The n-type second electrode covers the second passivation layer and the n-type first electrode, and the n-type second electrode is electrically connected to the n-type first electrode; The bonding substrate and the n-type second electrode are fixedly connected; The third passivation layer covers the surface of the AlN layer, and the p-type third electrode covers the third passivation layer and is electrically connected to the p-type second electrode.
2. The deep ultraviolet vertical structure light-emitting diode according to claim 1, characterized in that, The electrodes include one or more of gold, platinum, nickel, titanium, aluminum, chromium, palladium, silver, indium, copper, and tin.
3. The deep ultraviolet vertical structure light-emitting diode according to claim 1, characterized in that, The passivation layer comprises a single-layer or multi-layer composite layer composed of one or more of SiO2, Si3N4, ZrO2, and Al2O3. And / or, the bonding substrate layer includes a silicon substrate, a copper substrate, a ceramic substrate, or a metal composite substrate.
4. The deep ultraviolet vertical structure light-emitting diode according to claim 1, characterized in that, The thickness of the AlN layer is 50nm-4000nm; And / or, the thickness of the n-AlGaN layer is 1-3 μm; And / or, the thickness of the multi-quantum-well active layer is 30-100 nm; And / or, the thickness of the electron blocking layer is 20-50 nm; And / or, the thickness of the p-AlGaN layer is 100-200 nm; And / or, the thickness of the first passivation layer is 100-300 nm; And / or, the thickness of the second passivation layer is 200-500 nm; And / or, the thickness of the third passivation layer is 500-1000 nm.
5. The deep ultraviolet vertical structure light-emitting diode according to claim 1, characterized in that, The thickness of the n-type first electrode is 30-120 nm; And / or, the thickness of the n-type second electrode is 2μm-4μm; And / or, the thickness of the p-type first electrode is 50-200 nm; And / or, the thickness of the p-type second electrode is 600-1500 nm; And / or, the thickness of the p-type third electrode is 1μm-2μm.
6. A method for fabricating a deep ultraviolet vertical structure light-emitting diode according to any one of claims 1-5, characterized in that, Includes the following steps: (1) Epitaxial growth of a release layer, an AlN layer, an n-AlGaN layer, a multi-quantum-well active layer, an electron blocking layer and a p-AlGaN layer is performed sequentially on the substrate; (2) A first groove and a second groove are etched on the p-AlGaN layer, such that the first groove penetrates the p-AlGaN layer, the electron blocking layer, the multi-quantum well active layer and part of the n-AlGaN layer; the second groove penetrates the p-AlGaN layer, the electron blocking layer, the multi-quantum well active layer, the n-AlGaN layer and the AlN layer, exposing the release layer; (3) A first passivation layer is deposited on the surface of the p-AlGaN layer, the first groove and the second groove, and the first passivation layer is etched to expose the bottom n-AlGaN layer of the first groove and the bottom stripping layer of the second groove, and the first passivation layer is etched to expose the p-AlGaN layer to form a third groove, the third groove being located between the first groove and the second groove. (4) An n-type first electrode is prepared in the first groove, so that the n-type first electrode fills the first groove and extends the first passivation layer, and the n-type first electrode and the n-AlGaN layer are in ohmic contact. After preparation is completed, the first annealing treatment is performed. Then, a p-type first electrode is prepared in the third groove, so that the p-type first electrode fills the third groove and extends the first passivation layer, and the p-type first electrode and the p-AlGaN layer are in ohmic contact. After preparation is completed, a second annealing process is performed. A p-type second electrode is then prepared in the second groove, so that the p-type second electrode fills the second groove and extends out the first passivation layer and is electrically connected to the p-type first electrode. (5) A second passivation layer is deposited on the surface of the n-shaped first electrode, the p-shaped first electrode, the p-shaped second electrode and the first passivation layer, the second passivation layer is etched to expose the n-shaped first electrode, an n-shaped second electrode is prepared on the n-shaped first electrode, and the n-shaped second electrode is extended to cover the second passivation layer. (6) A metal layer is deposited on the surface of the bonding substrate, and the n-type second electrode and the bonding substrate are bonded by metal bonding process; (7) The substrate side is irradiated with a laser to thermally decompose the release layer and peel off the substrate layer, exposing the bare surface of the AlN layer and the p-type second electrode; a third passivation layer is deposited on the surface of the AlN layer and the bare p-type second electrode, the third passivation layer is etched to expose the p-type second electrode, and then a p-type third electrode is prepared on the bare p-type second electrode, and the p-type third electrode is extended to cover the third passivation layer.
7. The method for fabricating a deep ultraviolet vertical structure light-emitting diode according to claim 6, characterized in that, In step (4), the temperature of the first annealing is 850-900℃ and the time is 30-60s; And / or, the second annealing temperature is 500-550℃ and the time is 30-60s.
8. The method for fabricating a deep ultraviolet vertical structure light-emitting diode according to claim 6, characterized in that, In step (6), the metal layer includes one or more of Ti, Au, and In layers; And / or, the bonding temperature is 250-350℃, the bonding pressure is 1MPa-5MPa, and the bonding time is 10-30min.
9. The method for fabricating a deep ultraviolet vertical structure light-emitting diode according to claim 6, characterized in that, The substrate includes a sapphire substrate; And / or, the stripping layer includes a GaN stripping layer; And / or, the thickness of the release layer is 25-90 nm.
10. The method for fabricating a deep ultraviolet vertical structure light-emitting diode according to claim 6, characterized in that, In step (7), the wavelength of the laser is 193nm-355nm and the energy density is 200mJ / cm². 2 -1000 mJ / cm 2 Preferably, the laser is a KrF laser with a wavelength of 248 nm.